Synthesis and characterization of hybrid nanofluids from magnetite and gold nanoparticles - Haiza Haroon (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Nanofluids is a good candidate for heat transfer applications due to their anomalous thermal conductivity enhancement. Mixed nanofluids (MNs) also known as hybrid nanofluids based on mixture of magnetite, Fe3O4 and gold, Au nanoparticles were successfully developed in this work. Magnetite, Fe3O4 nanoparticles produced via Massart's procedure (a simple co-precipitation technique) were used to prepare water based magnetite ferrofluids without addition of any stabilizing agent or surfactant. Magnetic properties measured by vibrating sample magnetometer (VSM) at room temperature showed that magnetite nanoparticles are almost superparamagnetic with coercivity (Hc) value of 40.164 G. The saturation magnetization (Ms) of the magnetite nanoparticles was 61.864 emu/g which is lower than the bulk value of 92-100 emu/g. Five water based ferrofluids were prepared using different volume fractions of magnetite suspension 0.1, 0.05, 0.02, 0.01 and 0.005, respectively. Colloidal gold (Au) nanoparticles were synthesized using electro-dissolution-reduction method that consists of a simple two-electrode cells connected to a DC power supply. Throughout the process, bulk gold at the anode was oxidized into gold cations which then reacted with the chloride ions to form aurochloride complex. The complex ions were then reduced by the citrate ion to form colloidal gold nanoparticles. The parameters investigated are effects of terminal voltage and citrate concentration. The effects of these parameters on the particle size, shape and distribution were studied. For the effect of terminal voltage, the mean particle sizes obtained were 28.22 nm, 28.12 nm and 25.04 nm for 32 V, 36 V and 40 V, respectively from transmission electron microscope (TEM) analysis. For the effect of citrate concentration, the mean sizes of gold nanoparticles were 28.12 nm, 28.33 nm, 29.14 nm and 29.68 nm for 0.05 M, 0.10 M, 0.15 M and 0.20 M, respectively from TEM analysis. TEM micrograph showed that the shape of gold nanoparticles obtained was almost spherical with fairly good uniformity for effects of terminal voltage and citrate concentration. The thermal conductivity and suspension stability of ferrofluids, gold nanofluids and hybrid nanofluids were investigated in order to evaluate their potential application as heat transfer fluid. Thermal conductivity was measured at five different temperature, 25°C, 30°C, 40°C, 50°C and 60°C using KD2 Pro thermal property analyzer. Thermal conductivity increased as the temperature increases and reached its maximum at 60°C for all nanofluids samples. Ferrofluid prepared using 0.01 volume fraction of magnetite suspension demonstrated highest thermal conductivity enhancement of 49.4% with respect to water at temperature 60°C. Gold nanofluid prepared using 36 V terminal voltage exhibited highest thermal conductivity enhancement of 202.4% compared to water at temperature 60°C. Thus, this nanofluid suspension was selected and introduced to suspended magnetite nanoparticles to increase the thermal conductivity of hybrid nanofluids system. Hybrid nanofluids (HNF1) prepared using highest concentration of gold nanoparticles demonstrated substantial increase in thermal conductivity compared to other hybrid nanofluids that is 1.0794 Wm-1K-1 at 60°C. Overall, all hybrid nanofluids samples demonstrated excellent dispersion up to one week and relatively stable up to 2 weeks.